15-Lipoxygenases and its metabolites 15(S)-HETE and 13(S)-HODE in the development of non-small cell lung cancer. Issue 4 (13th April 2010) - Yuan, Huiling; Li, Ming-Yue; Ma, Lily T; Hsin, Michael K Y; Mok, Tony S K; Underwood, Malcolm J; Chen, George G
Abstract : Background: 15-S-Hydroxyeicosatetraenoic acid (15(S)-HETE) and 13-S-hydroxyoctadecadienoic acid (13(S)-HODE), both of which are metabolites of 15-lipoxygenases (15-LOXs), are endogenous ligands for peroxisome proliferator-activated receptor gamma (PPARγ). The activation of PPARγ inhibits cell growth and induces apoptosis in some cancers. The role of 15(S)-HETE) and 13(S)-HODE in the development of lung cancer is not clear. Methods: 15-LOXs, 15(S)-HETE and 13(S)-HODE were monitored during the development of mouse lung tumours induced by the tobacco smoke carcinogen 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) and the levels of these markers were determined in 54 human non-small cell lung cancers. Results: 15-LOXs, 15(S)-HETE and 13(S)-HODE levels were significantly reduced in human lung cancer tissue compared with non-tumour lung tissue (p=0.011 and p=0.022, respectively). In mouse experiments, 15(S)-HETE and 13(S)-HODE started to reduce at 26 and 30 weeks, respectively, after NNK treatment. The time frame of 15(S)-HETE reduction was in line with the decrease in 12/15-LOX mRNA and protein. A significant difference in the number of tumours in NNK-treated mice and controls was not observed until week 34 (p<0.05) and week 38 (p<0.01). The reduction in 12/15-LOX and 15(S)-HETE therefore predated the appearance of lung tumour. Furthermore, PPARγ activity was decreased in NNK-treated mouse lungs compared with the control, and the decreased PPARγ activity occurred at the same time points as the reduction in 12/15-LOX and 15(S)-HETE. Conclusion: These findings indicate that the reduction in 15-LOX, 15(S)-HETE and 13(S)-HODE results in the decreased PPARγ activity seen in lung tumours and contributes to the development of lung tumours induced by tobacco smoking.